2016
DOI: 10.3390/f7030056
|View full text |Cite
|
Sign up to set email alerts
|

A Review of the Characteristics of Small-Leaved Lime (Tilia cordata Mill.) and Their Implications for Silviculture in a Changing Climate

Abstract: Tilia cordata Mill. is a minor European broadleaved species with a wide but scattered distribution. Given its scarcity and low value in the wood market, it has received little attention from researchers and forest managers. This review summarizes the main aspects of T. cordata ecology and growth. Its main limiting factor is its need for warm summer temperatures to ensure successful seed production. It has a height growth pattern relatively similar to that of Acer pseudoplatanus L., with a slight delay in the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(51 citation statements)
references
References 72 publications
3
48
0
Order By: Relevance
“…Five individuals of A. rubrum and Q. rubra were available to compare to forest‐grown trees of those species and five individuals of littleleaf linden ( Tilia cordata Mill.) were available to compare to the forest‐grown T. americana ; these species are very similar in many of their traits, except for the size of the leaves of T. cordata (De Jaegere, Hein & Claessens ), and we did not incorporate leaves into comparisons of forest‐ and open‐grown trees. We selected only structurally sound individuals that had not been recently pruned or otherwise lost branches.…”
Section: Methodsmentioning
confidence: 99%
“…Five individuals of A. rubrum and Q. rubra were available to compare to forest‐grown trees of those species and five individuals of littleleaf linden ( Tilia cordata Mill.) were available to compare to the forest‐grown T. americana ; these species are very similar in many of their traits, except for the size of the leaves of T. cordata (De Jaegere, Hein & Claessens ), and we did not incorporate leaves into comparisons of forest‐ and open‐grown trees. We selected only structurally sound individuals that had not been recently pruned or otherwise lost branches.…”
Section: Methodsmentioning
confidence: 99%
“…Largely neglected indigenous broadleaved taxa such as Alnus, Tilia and Betula appear to be interesting alternative species. Some of them may be more adaptable to the future climate and could generate valuable products for future markets [9,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…A review of the research on Tilia cordata Mill. carried out by De Jaegere et al revealed that in Europe, the genetic diversity of T. cordata tends to decrease as latitude increases [ 49 ].…”
Section: Discussionmentioning
confidence: 99%